2001
DOI: 10.1097/00004347-200107000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Gastric Mucin and p53 in Minimal Deviation Adenocarcinoma of the Uterine Cervix

Abstract: Comparative immunostaining with antibodies against gastric mucin and p53 was performed on 6 cases of minimal deviation adenocarcinoma (MDA) of the uterine cervix. The MDAs consisted of predominant areas of glands lined by extremely well-differentiated tall columnar epithelial cells with little cytological atypia and minor foci of less well-differentiated glandular epithelium with a minor degree of nuclear atypia. Immunostaining for gastric mucin with a monoclonal antibody HIK1083 revealed that all the tumors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…These authors also found a molecular-genetic link between LEGH and cervical mucinous glandular malignancies, including MDA and MAC, and suggested that some LEGH lesions are precursors of MDA and/or MAC lesions. A close association between synchronous mucinous metaplasia and neoplasms of the female genital tract (SMMN-FGT) and LEGH/pyloric gland metaplasia (PGM) was verified by Mikami et al [24], and Ichimura et al [16] consider MDA to be a malignant conversion of endocervical glands now expressing gastric mucin. They also suggest that the expression level of p53 may be an indicator of the local progression of MDA.…”
Section: Discussion and Reviewmentioning
confidence: 92%
See 1 more Smart Citation
“…These authors also found a molecular-genetic link between LEGH and cervical mucinous glandular malignancies, including MDA and MAC, and suggested that some LEGH lesions are precursors of MDA and/or MAC lesions. A close association between synchronous mucinous metaplasia and neoplasms of the female genital tract (SMMN-FGT) and LEGH/pyloric gland metaplasia (PGM) was verified by Mikami et al [24], and Ichimura et al [16] consider MDA to be a malignant conversion of endocervical glands now expressing gastric mucin. They also suggest that the expression level of p53 may be an indicator of the local progression of MDA.…”
Section: Discussion and Reviewmentioning
confidence: 92%
“…Pathologists are using immunohistochemistry in their efforts to distinguish MDA from benign proliferating diseases of the cervical glands. Carcinoembryonic antigen (CEA), Ki67, alcian blue-periodic acid-Schiff staining (AB/PAS), HIK1083 [15,16], and smooth muscle actin (SMA) [17] helped in diagnosing MDA in the reviewed case reports, and these markers are therefore important. Surgical treatment, however, remains the best choice.…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…Frequent p53 protein overexpression has also been reported in cases of MDA. 49 Therefore, in cases of GAC, p53 as well as a variety of gene alterations might play a role in carcinogenesis distinct from HPV-related AC. A more detailed understanding of its molecular mechanisms is expected to improve the outcome from treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HIK1083 appears to be quite specific in the distinction of gastric‐type EA from its endometrial mimics. However, like MUC6, HIK1083 is also not diffusely or universally expressed in gastric‐type EAs . Therefore, lack of expression in a tumour does not rule out a gastric‐type EA.…”
Section: Discussionmentioning
confidence: 99%